Pengaruh Remunerasi Terhadap Kinerja Pegawai Pada Biro Umum Sekretariat Jenderal Kementerian Perhubungan - Wasti Rachmawaty; Pandoyo (CV ODIS, 2020)
Remuneration governance is an integral part of Policy Reforms. Background by awareness at the same time the government's commitment to bring clean and good governance. But at the level of implementation, change and renewal are implemented in order to realize clean governance and the authority may not be able to be implemented properly (effectively) without the proper welfare of the personnel who carry it out. The problems discussed in this study is how much influence the Remuneration on Employee Performance In General Bureau of the Secretariat General of the Ministry of Transportation. The method used in this study is a quantitative method using correlation analysis techniques and the coefficient of determination. The population in this study is 279 people and a sample of the entire population of 70 people. Data were collected by questionnaires. Results calculated product-moment correlation coefficient was 0.5918 and the calculation of the coefficient of determination equal to 34.06%. The remaining amount of 65.04% is influenced by other variables outside of research such as Leadership, Organizational Culture, and Competence.